Processing of zinc oxide varistors : sources of defects and possible measures for their elimination - Karim, A. N. Mustafizul; Begum, Shahida; Hashmi, M. S. J. (Elsivier Science B. V., 1997)
The processing of ZnO varistors primarily follows the conventional ceramic route. A number of dopants are added to zinc oxide powder to prepare the constituent material and some additional finishing operations are performed for securing the varistor action. Thus there involved a large number of processing operations and there are naturally multiple sources from which defects can originate. To quality a varistor performance several parameters are commonly investigated of which energy absorption capability of the device is a significant one. In this respect flaws and defects developed in the varistor body during the processing have detrimental effects and can considerably restrict the energy absorption capability. This paper briefly outlines the probable sources of defects of the metal-oxide varistor device and their possible solutions mainly with sintering orientation, passivation thickness and electrode area.